Rehabilitation Reconsidered: A Comprehensive Legal Analysis (Journal of Asian Development Studies, 2023)
This research article delves into the multifaceted realm of rehabilitation from a legal perspective. Rehabilitation, a fundamental aspect of the criminal justice system, plays a pivotal role in promoting societal reintegration and reducing recidivism. This paper examines the legal dimensions of rehabilitation, including its conceptualization, implementation, and impact within the criminal justice context. The article begins by providing a comprehensive overview of the historical and philosophical foundations of rehabilitation in the context of the law. It delves into the changing paradigms of punishment and the evolving understanding of rehabilitation's role in promoting individual transformation and societal safety. Furthermore, the paper explores the legal frameworks and mechanisms that support rehabilitation within various legal systems, analyzing legislative provisions, case law, and the role of judicial discretion. It examines the challenges and opportunities presented by rehabilitative efforts, especially in balancing individual rights and societal interests. The discussion extends to critically examining the effectiveness of rehabilitation programs and initiatives in achieving their intended goals. Through a review of empirical studies and legal analysis, this article assesses the impact of rehabilitation on recidivism rates, public safety, and the overall success of the criminal justice system. The qualitative research methodology has been applied to the following article.